Karl Barth: um chamado cristão a desobediência civil - Silva, Julio César Silveira da (2011)
Karl Barth (1886 - 1968), a native of Basel, Switzerland, was a Reformed theologian and pastor of exponential expression. Barth had his theological education guided by the primary matrix of theological liberalism. During the First World War, however, before the calamity that has taken place, Barth became disenchanted with the liberal Protestant horizon, with its modern worldview, his theology and his immanentist utopia of social redemption grounded in belief in the progress of reason. The result was the rapprochement of Barth with classical Reformed tradition and the emergence of a theological approach that rescues principles of Christian orthodoxy and updates them with elements of modernity, namely the neo-orthodoxy. However, with the transcendent criterion not reason or aesthetics, but the Word of God attested in Scripture, and Jesus, understood as the incarnation of God as a hermeneutical key. The object of the dissertation, in its material dimension, is the Declaration of Barmer, and in its formal dimension, Barthian theology. The dissertation aims to analyze the historical and political conditions that favored the accession of the German Evangelical Church to the Nazis, and the correlation of positive theological presuppositions of Christianity with the liberal Protestantism. The course in research allows us to conclude that whenever theology loses a sense of the transcendent character and extraordinary revelation, human words are taken as divine. And this is not no harm to the Christian faith. Barth's theology provides a great service by emphasizing the transcendence of God's Word to all human words. Despite dialectically to use them to communicate, it transcends them and puts them into crisis, because it is perfect and eternal as the theologies, philosophies, ethics and policies are imperfect and incomplete. Therefore, the Christian community should be aware that if he wants to be faithful to her calling, she can never align itself automatically to any creed or political party and ideology, but to the Gospel